TUBE THOROCOSTOMY: MANAGEMENT AND OUTCOME IN PATIENTS WITH PENETRATING CHEST TRAUMA - Muslim, Muhammad; Bilal, Amer; Salim, Muhammad; Khan, Muhammad Abid; Baseer, Abdul; Ahmed, Manzoor (Journal of Ayub Medical College Abbottabad, 2008)
Background: Penetrating chest trauma is common in this part of the world due to present situation in tribal areas. The first line of management after resuscitation in these patients is tube thoracostomy combined with analgesia and incentive spirometry. After tube thoracostomy following surgery or trauma there are two schools of thought one favours application of continuous low pressure suction to the chest tubes beyond the water seal while other are against it. We studied the application of continuous low pressure suction in patients with penetrating chest trauma. This Randomized clinical controlled trial was conducted in the department of thoracic surgery Post Graduate Medical Institute Lady Reading Hospital Peshawar from July 2007 to March 2008. The objectives of study were to evaluate the effectiveness of continuous low pressure suction in patients with penetrating chest trauma for evacuation of blood, expansion of lung and prevention of clotted Haemothorax. Methods: One hundred patients who underwent tube thoracostomy after penetrating chest trauma from fire arm injury or stab wounds were included in the study. Patients with multiple trauma, blunt chest trauma and those intubated for any pulmonary or pleural disease were excluded from the study. After resuscitation, detailed examination and necessary investigations patients were randomized to two groups. Group I included patients who had continuous low pressure suction applied to their chest drains. Group II included those patients whose chest drains were placed on water seal only. Lung expansion development of pneumothorax or clotted Haemothorax, time to removal of chest drain and hospital stay was noted in each group. Results: There were fifty patients in each group. The two groups were not significantly different from each other regarding age, sex, pre-intubation haemoglobin and pre intubation nutritional status. Full lung expansion was achieved in forty six (92%) patients in group I and thirty seven (74%) in group II. Partial lung expansion or pneumothorax was present in three (6%) in group I and 10 (20%) in group II. One patient in group I and three (6%) patients in group II had no response. The mean time to removal of chest drains were 8.2±3.14 days in group I and 12.6±4.20 days in group II. The length of hospital stay was 7.2±2.07 days and 12.4±3.63 days in group I and II respectively. Clotted Haemothorax requiring surgery developed in three (6%) patients in group I and 8 (16%) patients in group II. Conclusion: Placing chest tubes on continuous low pressure suction after penetrating chest trauma helps evacuation of blood, expansion of lung and prevents the development of clotted Haemothorax. It also reduces the time to removal of chest drains, the hospital stay and the chances of surgery for clotted Haemothorax or Empyema. Keywords: Penetrating chest trauma, low pressure suction, clotted Haemothorax, lung expansion, pneumothorax, tube thoracostomy.